Structure of the dual mode Wnt regulator Kremen1 and insight into ternary complex formation with LRP6 and Dickkopf - Jones, E; Zebisch, M; Jackson, V; Zhao, Y (Cell Press, 2016)
Kremen (Krm) 1 and 2 have been identified as co-receptors for Dickkopf (Dkk) proteins, hallmark secreted antagonists of canonical Wnt signalling. We present here three crystal structures of the ectodomain of human Kremen1 (KRM1ECD) at resolutions between 1.9 and 3.2 Å. Krm1ECD emerges as a rigid molecule with tight interactions stabilizing a triangular arrangement of its Kringle (KR), WSC and CUB structural domains. The structures reveal an unpredicted homology of the WSC domain to hepatocyte growth factor. We further report the general architecture of the ternary complex formed between the Wnt co-receptor Lrp5/6, Dkk and Krm determined from a low resolution complex crystal structure between β-propeller / EGF repeats (PE) 3 and 4 of the Wnt coreceptor LRP6 (LRP6PE3PE4), the cysteine-rich domain 2 of DKK1 (DKK1CRD2) and KRM1ECD. DKK1CRD2 is sandwiched between PE3 of LRP6 and the KR-WSC domain pair of KRM1. Modelling studies supported by surface plasmon resonance (SPR) suggest a direct interaction site between Krm1CUB and Lrp6PE2.